The Decline of Local Political Parties in Post-Conflict Aceh: A Qualitative Study - Siti Ikramatoun; Zulfan Zulfan; Aminah Aminah (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
The Aceh peace process has been ongoing for nearly two decades. Some studies note that an essential aspect contributing to the Aceh peace context is the presence of local political parties in the post-peace era. This article aims to describe the declining existence of local political parties in the political life of Aceh society. This study employs a qualitative method, with primary data obtained from interviews and secondary data gathered from relevant literature reviews. The study reveals that local political parties in post-conflict Aceh have essentially gone through three of the four phases and are beginning to enter the fourth. The first phase is the formation of local political parties, the second is their rise, and the third is their victory in Aceh's political contestation. The fourth phase is decline or reduction, characterized by local parties being abandoned by their supporters. This research identifies several factors indicating the current existence of local political parties in the decline phase: 1) Loss of public trust; 2) Pessimism among political actors; 3) Weak party integrity and human resources; 4) Unprofessional organizational management; and 5) Internal conflicts within the party. These factors are not independent but are interconnected with one another.